Metacordyceps shibinensis sp. nov. from larvae of Lepidoptera in Guizhou Province, southwest China - Wen, Tingchi; Zha, Ling-Sheng; Xiao, Yuan-Pin; Wang, Qiang; Kang, Ji-Chuan; Hyde, Kevin D. (Phytotaxa, 2015)
A new entomogenous taxon, Metacordyceps shibinensis sp. nov., associated with a larva of Lepidoptera was found in Yuntai Mountains, Guizhou Province, China. It differs from similar species in its white to faint yellow stromata, short ascomata, and very short asci and ascospores. Combined sequence analyses of 5.8S-ITS rDNA, nrSSU, EF-1α and RPB1 gene-loci also confirmed the distinctiveness of this new species.